Macro Approach in Education Strategic Planning: Implications For Sustainable Development at Sman 1 Kawali - Khadijah, Ifah; Rahayu, Noneng Sri; Khendrayati, Rika; Risthiany, Ressy; Juandi, Aa Budi (Universitas Muhammadiyah Ponorogo, 2025)
Applying the macro approach in education strategic planning at SMAN 1 Kawali aims to support sustainable development by integrating sustainability principles into the curriculum. Education has a strategic role in raising students' awareness and engagement with environmental issues, as well as strengthening collaboration with external stakeholders such as parents and communities. This research used a descriptive qualitative approach with interview, observation, and documentation study methods. Data were collected from the principal, teachers, and students at SMAN 1 Kawali to explore the implementation of the macro approach and its impact on student engagement in sustainable education. Data analysis was done thematically to identify patterns and relationships in the implementation of school programmes. The results show that the macro approach in education strategic planning positively impacts student engagement. Integrating sustainability principles in the curriculum increases students' awareness of environmental issues and encourages them to actively participate in learning. In addition, collaboration between the school and external stakeholders has created a sense of ownership and responsibility for the environment. The project-based learning approach proved effective in improving students' motivation and academic achievement. The implementation of the macro approach at SMAN 1 Kawali contributes to increased student engagement and effectiveness of sustainable education. However, challenges in measuring long-term impact as well as limitations in the scope of the study need to be addressed. Further research is needed to explore similar implementations in other schools and develop more relevant evaluation indicators to support education sustainability.